Environmental norms, society, and economics - Ernst Mohr (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
Environmental norms seem to be on the upsurge everywhere. Norm-orientation is, however, neglected in neoclassical economics which is fixed on homo economicus as the model of human behaviour. The paper addresses the question whether homo economicus needs to give way to a norm-oriented concept in environmental economics. This question is tackled in an interdisciplinary and evolutionary approach. Using economic concepts, forces are identified which are detrimental to or which promote environmental norms in the process of civilisation. This investigation provides some clues on the likely importance of environmental norms in a future ecologically oriented society. These clues provide in turn one answer to the fundamental question posed, whether the neoclassical concept of human behaviour will likely remain or cease to be the 'standard' tool in environmental economics. Rather .than tackling the question in greatest generality the analysis takes recourse to an example: the problem of the commons. The commons is particularly suited for this investigation because it is well roamed by all the disciplines which are of relevance for the undertaking.
Keywords: 330; Umweltökonomik; Rationales Verhalten; Soziale Werte; Allmenderessource; Theorie